2020
DOI: 10.1186/s12870-020-02582-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analyses reveal different mechanism of high- and low-tillering genotypes controlling tiller growth in orchardgrass (Dactylis glomerata L.)

Abstract: Background: Tillering is an important agronomic trait underlying the yields and reproduction of orchardgrass (Dactylis glomerata), an important perennial forage grass. Although some genes affecting tiller initiation have been identified, the tillering regulatory network is still largely unknown, especially in perennial forage grasses. Thus, unraveling the regulatory mechanisms of tillering in orchardgrass could be helpful in developing selective strategies for high-yield perennial grasses. In this study, we ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The regulation mechanism of plant tillering has been revealed from analysis of hormones, genes and transcription, which has provided a basis for the study of forage yield formation, environmental adaptation and the survival competitiveness of gramineous plants. Xu et al (2020) reported that approximately 13,609 DEGs were identified from a high-tillering genotype and a low-tillering genotype of Orchard grass. In this research, P. juncea with dense tillers and sparse tillers were selected for transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation mechanism of plant tillering has been revealed from analysis of hormones, genes and transcription, which has provided a basis for the study of forage yield formation, environmental adaptation and the survival competitiveness of gramineous plants. Xu et al (2020) reported that approximately 13,609 DEGs were identified from a high-tillering genotype and a low-tillering genotype of Orchard grass. In this research, P. juncea with dense tillers and sparse tillers were selected for transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…2). Xu et al [44] reported that ploidy was not associated with a hightillering and a low-tillering phenotype of Orchardgrass. Abundant researches have shown that the tiller number is related to the tiller angle [50,51].…”
Section: Phenotypic Differences Between Dense and Sparse Tillering P ...mentioning
confidence: 99%
“…In addition, many of these DEGs were highly expressed in the tiller node tissues of DT compared with ST, which might be responsible for the difference in tiller phenotypes. Xu et al [44] analyzed transcriptome of different organs of orchardgrass, including tiller buds, shoot base, root and leaf tissues, and found that tiller buds had the most DEGs compared with other organs. Moreover, tiller buds had more tiller regulation pathways (such as hormone regulation and biosynthesis of lignin) than other organs.…”
Section: Candidate Genes and Regulatory Processes Involved In Tiller ...mentioning
confidence: 99%
See 1 more Smart Citation
“…GA is involved in the regulation of tillering, but its effect on tillering (branch) is different in different species. Previous studies found that GA might promote tillering/branch in perennial woody plants, such as sweet cherry [ 13 ] and Jatropha curcas [ 14 ], but inhibit tillering/branch in annual herbaceous plants, such as tall fescue [ 15 ], orchardgrass [ 16 ] and tomato [ 17 ]. Previous studies confirmed that CTK improves tillering development [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%